A 2‐D observer to estimate the reaction rate in a stopped flow fixed bed reactor for gas phase olefin polymerization. Issue 10 (5th July 2014) - Browning, Barbara; Sheibat‐Othman, Nida; Pitault, Isabelle; McKenna, Timothy F. L.
<x xml:space="preserve">Abstract</x> A two‐dimensional high gain observer has been constructed to estimate the reaction rate parameters in a laboratory scale stopped flow fixed bed reactor for gas phase ethylene polymerization. The observer is based on the heat balances of a validated model of the reactor and the measured variable is the outlet temperature of the fixed bed. To create an observable system of equations, the polymerization rate is considered in two parts, an activation energy term and a lumped parameter. The effective radial conductivity in the fixed bed and the heat‐transfer coefficient at the wall are considered separately. The polymerization rate is calculated from the observer results and is in good agreement with the measured data and calculated values. © 2014 American Institute of Chemical Engineers AIChE J, 60: 3511–3523, 2014